29.1k views
3 votes
A - g(x) = |x-5|+5
B - g(x) = |x-5|
C - g(x) = |x|+5
D - g(x) = |x+5|+5

A - g(x) = |x-5|+5 B - g(x) = |x-5| C - g(x) = |x|+5 D - g(x) = |x+5|+5-example-1
User Mobin
by
5.8k points

1 Answer

7 votes

Answer:


g(x) = |x| + 5

Explanation:

Since both the original and transformed graph have the same x value for their vertex, there was no horizontal shift. However the vertex shifted up. Specifically it shifted up 5 units. Therefore:


g(x) = f(x) + 5

The plus 5 performs a translation up 5 units. Plugging in for f(x) it can be seen that:


g(x) = |x| + 5

User Barbaros
by
6.5k points